Access & equity challenges for open and distance learning - Asian Association of Open Universities. Conference New Delhi, India) 2002n; Dikshit, H. P.; Indira Gandhi National Open University (New Delhi Kogan Page India, 2002)
Contributed articles of the Fifteenth Conference of Asian Association of Open Universities, held by Indira Gandhi National Open University.
Keywords: Distance education -- Asia -- Congresses; Open learning -- Asia -- Congresses